How to teach entrepreneurship education to culinary students? Case studies of school enterprise program in Indonesia - Saputro, Ida Nugroho; Mahfud, Tuatul; Mulyani, Yogiana; Nurtanto, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The study of entrepreneurial learning in schools has been widely reviewed, however, is limited to aspects of the theory. This study aims to find out how to teach entrepreneurship education in culinary schools. This study used a qualitative approach with case studies design. The result revealed that: (1) entrepreneurship education is considered very important to create new jobs in the culinary field; (2) entrepreneurial learning in culinary schools requires experiential learning (e.g., school enterprises); (3) the goal of the school enterprise program is to obtain funding sources to finance school program (short-term) and train students to become self-employees (long-term). The findings of this study discuss in depth and some implications for vocational education practitioners proposed for further improvement in entrepreneurial learning. The implication was that entrepreneurship learning in vocational schools requires a relationship between entrepreneurship education and student vocational skills.